Analisis Semiotika Feminisme Radikal dalam Film Poor Things - Muslimin, Nada Musfikin; Muna, Naelul (Fakultas Ekonomi dan Ilmu Sosial Program Studi Ilmu Komunikasi Universitas AMIKOM Yogyakarta, 2024)
The issue of feminism has been a topic of intense and in-depth discussion in various circles, involving a variety of perspectives in academic, social, and cultural studies. Social dynamics that occur such as social class injustice based on gender, oppression of women, sexism, patriarchal ideology that defines women as objects of sexuality and so on make this issue raised in any media, one of which is film. In this study, researchers are interested in analyzing the film Poor Things directed by Yorgos Lanthimos from a script by Tony McNamara which highlights women having freedom over their bodies, the setting of this film was taken in the Victorian era where at that time women were considered a second class that functioned to satisfy male sexual urges. This research aims to explain the meaning of the semiotic code of radical feminism in Poor Things directed by Yorgos Lanthimos from a script by Tony McNamara which highlights women having freedom over their bodies. The method used in this research is a qualitative approach with John Fiske's semiotic analysis based on codes that are divided into three levels, namely the level of reality, representation and ideology. The results show the values of radical feminism at the level of reality through the codes of appearance, makeup, costumes, speech, environment and behavior. At the representation level, the values of feminism are shown through the codes of camera, character, action, conflict and dialog. At the ideological level, radical feminism found in the movie Poor Things is included in patriarchal ideology. In the movie Poor Things, the level of ideology displayed is patriarchy where women are considered as a second class that functions to satisfy men's sexual urges.